Resgatando alguns teoremas clássicos da geometria plana - Macedo, Darilene Maria Ribeiro (2014)
The study of geometry provides a rich and attractive field of manipulatives, because geometry is present in the daily life of all people, sometimes explicitly and sometimes in a subtle way. We present, however, in this work, many situations that show that geometry goes much beyond mathematical equations. We intent to make a simple approach of some triangles-related theorems, focusing on Stewart’s, Ceva’s, Menelaus’ and Napoleon’s, as well as on their detailed demonstrations in a comprehensive way. Having as one of the goals to make those more spread, in such a way that they can be used as complementary tools to help the learning of plane geometry. For even being such a great key to many questions’ solutions, they are not usually applied. Finally, we conclude this work with some applications, which will hopefully excite and whet the curiosity of the reader to search for more.